Jackson Elementary School Christmas Show - Watkins, Howard::::::::: (1983)
In audience: Greg Wille, Cathy Wille holding Maya Wille on lap, Devon Bleile-Kratzer, Nancy Bleile holding Annie Bleile-Kratzer